2020
DOI: 10.1186/s12912-020-00418-w
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy, digital literacy and eHealth literacy in Danish nursing students at entry and graduate level: a cross sectional study

Abstract: Background: The increasing number of people living with one or more chronic conditions imposes a growing demand on healthcare providers. One way to handle this challenge is by re-orientating the way care is provided, empower people and increase their ability to manage their condition. This requires, amongst other factors, sufficient level of health literacy (HL) and digital competences among both patients and the healthcare providers, who serve them. The focus of this study is the level of HL, digital literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 38 publications
9
61
4
1
Order By: Relevance
“…This in contrast to other results. Final year nursing students showed signi cantly higher self-related health than the rst year students [33] did. As students progressed in their nursing studies, they showed improved health practices including more exercises and dietary practices [35].…”
Section: Health Practice Per Year Of Studymentioning
confidence: 74%
See 1 more Smart Citation
“…This in contrast to other results. Final year nursing students showed signi cantly higher self-related health than the rst year students [33] did. As students progressed in their nursing studies, they showed improved health practices including more exercises and dietary practices [35].…”
Section: Health Practice Per Year Of Studymentioning
confidence: 74%
“…Gender, marital status and chronic disease status were not correlated to health literacy. Previous studies con rm that age signi cantly in uences health literacy [33] and con rms that gender do not determine the level of health literacy [31] as well as having a chronic disease or not [33]. However, gender has been found to show differences in health literacy levels among nursing students [26].…”
Section: Determinants Of Health Literacy and Health Practicementioning
confidence: 99%
“…Among nursing student samples, a low or inadequate self-perceived level of eHealth literacy was reported in Ethiopia [14] and Sri Lanka [15] while moderate eHealth literacy was disclosed with nursing students in Jordan [2], Nepal [3], and Japan [16]. On the other hand, nursing students in Korea [10] and Denmark [17] reported satisfactory eHealth literacy. A comparison of American and Korean nursing students' eHealth literacy found that nursing students in the US posted higher mean scores of eHealth literacy [1].…”
Section: Annals Of Tropical Medicine and Publicmentioning
confidence: 95%
“…In spite of advantages mentioned for mt, some disadvantages have also been reported by some studies. The mt quality highly depends on subject area, text type, size as well as language pair which imposes limitations on the quality of the output generated by mt (Godwin-Jones, 2015;Holt, Overgaard & Engel, 2020). Some studies (Shei, 2002a(Shei, , 2002b have shown that there are limitations regarding mt pre-editing at cultural, lexicosemantic and idiomatic levels.…”
Section: Literature Reviewmentioning
confidence: 99%